Customary law in the digital era: Safeguarding indigenous sovereignty in cyberspace - Nandari, Ni Putu Sawitri; Rama, Bagus Gede Ari (ARKA INSTITUTE, 2025)
This study examines the adaptation of customary law in the digital era and the legal protection of indigenous digital rights. Despite constitutional recognition in Article 18B(2) of the 1945 Constitution, the absence of specific regulations on communal digital data ownership exposes indigenous communities to risks of exploitation and marginalization. Using a normative legal method with statutory, conceptual, and comparative approaches, this study analyzes national and international legal frameworks, including UNDRIP (2007) and ILO Convention No. 169, while comparing regulatory models from Canada, New Zealand, and Australia. Findings indicate that while digitalization facilitates the preservation of customary law, it also enables unauthorized data use and limits indigenous participation in digital policymaking. Solutions such as blockchain-based documentation and community-driven licensing offer potential legal safeguards. This study concludes that legal reforms are needed to ensure explicit recognition of communal digital rights, integration of indigenous dispute resolution in digital law, and stronger indigenous participation in digital policymaking, reinforcing legal pluralism in the digital era.